Perkembangan Motorik Halus Anak Usia Pra Sekolah 4-5 Tahun dengan Kegiatan Montase - I Made Sundayana; Kadek Yudi Aryawan; Putu Cyndy Fransisca; Ni Made Dwi Yunica Astriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to analyze the effect of montage activities on the fine motor development of pre-school aged children 4-5 years. The research method used was pre-experimental with one group pre and post test design. The results showed an average pre-test value was 43.44 and the post-test mean value was 68.21. Paired Sample T-test results obtained Ï-value (0,000) <Î± (0.05), there is the effect of montage activity on fine motor development in pre-school age children 4-5 years. Conclusion, fine motor is a limited movement of parts that include small muscles, especially movements of the fingers such as writing, drawing, and holding something. Keywords: Children 4-5 Years Old, Montage Activities, Fine Motor Development